Electrode, method for producing same, and primary or secondary energy storage device or electrochemical cell
By forming a covalently bonded multilayer structure on the surface of chalcogenide-based battery electrodes, the deficiencies in electronic conductivity and cycle performance of existing batteries are solved, and more efficient electrochemical energy storage is achieved.
Patent Information
- Application Number
- CN202411291277.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-18
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-24
AI Technical Summary
Existing chalcogenide-based batteries, especially lithium-sulfur batteries, have problems such as poor electronic conductivity, insufficient cycling performance and rate performance, resulting in insufficient utilization of active materials and capacity attenuation.
It is formed by forming a covalently bonded insoluble copolymeric "shell" composed of glass/polymer/amorphous chalcogenides and crystalline sulfur allotropes on the electrode surface, combined with a transition layer of reduced graphene oxide. Density gradient structure to buffer volume changes.
It improves the electronic and ionic conductivity of the electrode, buffers volume expansion, reduces polysulfide dissolution during cycling, and significantly improves the cycle stability and rate performance of the battery.
Smart Images

Figure CN119361602A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure generally relates to electrodes and / or cathodes and methods of producing electrodes and / or cathodes. The present disclosure specifically addresses the most critical drawbacks of existing alkali ion / chalcogenide batteries as it integrates the beneficial properties of crystalline and glass / polymer / amorphous chalcogenide active materials, capable of forming / coexisting as glass / polymer / amorphous and crystalline phases, wherein surface-driven proton / electron induced ring-opening polymerization (ROP) forms a thin layer of chemically bonded insoluble copolymeric "shell" that protects a "crystalline core", wherein such layer behaves as a non-removable protective transition layer for mixed ionic and electronic conductivity, resulting from a chemical / covalently bonded "core-shell strategy". Background Art
[0002] Metal-sulfur (MS) batteries are considered promising candidates for next-generation energy storage. However, the practical implementation of such MS batteries, such as lithium-sulfur (Li-S) technology, is limited by the insulating nature of sulfur (electronic conductivity ~10 at room temperature). - 30 S.cm -1 ) and its low utilization factor, which is due to its low ionic conductivity of 10 –13 S.cm -1 and due to the intermediate lithium polysulfide (PSs) (Li2S n ,4≤n≤8) resulting in severe capacity decay during cycling (charge / discharge).
[0003] The poor electronic conductivity of sulfur and the shuttling of PSs result in insufficient utilization of active materials, leading to unfavorable rate performance and capacity decay. To overcome the above disadvantages, sulfur is usually impregnated / encapsulated in conductive porous matrices, such as porous carbon, graphene, carbon nanotubes, metal-organic frameworks, and / or mixtures of different conductive host structures, to accelerate electron transfer, buffer volume expansion, and mitigate polysulfide dissolution.
[0004] Even after some significant advances, chalcogenide-based electrodes, such as sulfur-containing cathodes, still suffer from poor electronic conductivity, insufficient cycling performance, and insufficient rate capability.
[0005] In state-of-the-art slurry-based sulfur-containing cathodes, electrons and ions (e.g. Li +) are transported through a percolation network formed by a stochastically driven process, where the main building blocks are particles-aggregates-clusters (PACs) composed of redox-active materials (also called sulfur / sulfur species), polymers or mechanical binders such as single-walled carbon nanotubes (SWCNTs) or other electronic and / or ionic conductive and processing additives. In order to operate at an acceptable utilization factor, the w / v content of the conductive additive in such an electrode (cathode) must reach a certain wt.% to break through the percolation threshold, beyond which the electrode (cathode) will obtain sufficient electronic and / or ionic conductivity. For example, sulfur-based cathodes produced by inverse vulcanization are known to have low active mass content because suitable cross-linkers or co-monomers are required to complete sulfur copolymerization in precise proportions. Typically, the wt. ratio is about 80% sulfur and 20% cross-linker such as 1,3-diisopropylbenzene (DIB), forming poly(sulfur-random-(1,3-diisopropenylbenzene)) copolymers, also known as poly(Sr-DIB).
[0006] The object of the present disclosure is to provide a stable chalcogenide-rich electrode, ideally a sulfur-rich cathode, which provides improved electronic and / or ionic conductivity, can buffer any volume changes, and mitigate polysulfide dissolution during cycling. The electrode can be used in electrochemical energy storage devices, such as primary and / or secondary rechargeable batteries containing alkali and / or alkaline earth (Li, Na, K, Ca, Mg, etc.) and / or Al metal / ions and / or Zn metal / ions and / or Ca metal / ions, for example, high-energy Li-S batteries, Na-S batteries, Mg-S batteries, Al-S, Zn-S batteries, or Ca-S batteries. Further objects will become apparent based on the following description. Another aspect of the present disclosure is the presence of sulfur S after photon and / or electron irradiation. x ● The free radicals then induce the selective reduction of GO to reduced graphene oxide (rGO) at the interface between sulfur and GO, wherein there are still residual mainly negatively charged functional groups on the surface, which are able to react with suitable comonomers and / or provide doping for conjugated polymers such as PEDOT and / or provide shielding / repulsion for negatively charged polysulfides, thereby limiting the diffusion / migration of polysulfides from the cathode.
[0007] The presence of highly thermally conductive rGO (800 W / mK) and low thermally conductive sulfur (0.12 W / mK) on the surface enables the formation of a thermal gradient between the core / shell so that during the subsequent quenching process, the solidification of the preferred monoclinic sulfur allotrope propagates from the rGO-S stable polymer shell to the crystalline core. The difference between the density of the glassy / amorphous / polymer and crystalline allotropes of sulfur allows the introduction of a density gradient, which acts as a buffer for volume expansion during the cycle. For example, a non-removable, chemically bonded, ionically and electronically conductive protective layer for a porous sulfur wafer / cathode (Theion: WO 2021 / 233965 A1) comprising a monoclinic (β- and / or γ-phase) sulfur allotrope is realized to realize an electrochemical energy storage device containing alkali and / or alkaline earth (Li, Na, K, Ca, Mg, Al, Zn, etc.) metals / ions, such as a Li-S battery, or a Na-S battery, or a Mg-S battery, an Al-S, a Zn-S battery, or a Ca-S battery. Summary of the invention
[0008] The present disclosure relates to an electrode and / or cathode stabilized, for example, by a transition layer (which may also be referred to as a first coating), comprising at least one of:
[0009] (a) a porous chalcogenide-based electrode (or porous chalcogenide-based electrode material), e.g. sulfur, e.g. comprising (or consisting essentially of) a crystalline (e.g. sulfur) allotrope within a core (i.e. the core of the electrode), wherein optionally a shell may cover the surface of the electrode material and / or the core;
[0010] (b) at least one of a glass, a polymer and an amorphous chalcogenide such as a sulfur allotrope, present in a transition layer and / or a shell covering the surface of an electrode material (i.e., an active electrode material), the transition layer comprising, for example, a two-dimensional (2D) material, a chalcogenide such as sulfur of the electrode material being covalently bonded therebetween, and, for example, 12 wt% or less of polymeric sulfur based on the total weight of the coated electrode; and
[0011] (c) a coating layer on top of the transition layer, the coating layer comprising, for example, a 2D material,
[0012] (d) for example, there is a density gradient between the crystalline core and, for example, the glass / polymer / amorphous shell (in one example, item (d) may also be an optional consequence of the electrodes of the present disclosure),
[0013] (e) an electrode (which may be an electrode of the present disclosure or a portion of an electrode of the present disclosure), wherein the volume of the crystalline allotrope present in the internal voids (i.e., the volume occupied by the crystalline allotrope) represents a buffer volume for compensating for volume fluctuations during battery cycling (in one example, item (e) may also be an optional result of the electrode of the present disclosure),
[0014] (f) a chalcogenide electrode (which may be an electrode of the present invention or a part of an electrode of the present invention), such as a sulfur-rich electrode, wherein the electrode active material is composed of binary and / or ternary dopants such as selenium, tellurium, having the composition (SexSy), (TexSy), (TexSySez), wherein the mass content of sulfur in the cathode may be higher than 50% per weight of the total chalcogenide content.
[0015] (g) In addition, the coated electrode and / or cathode may include, for example, at least one sulfur allotrope that may be doped with a chalcogenide, a halogen, or a mixture thereof, for example, from 0.001 to 50 wt % of the chalcogenide, the halogen, or a mixture thereof, such as 0.01 to 49 wt %, 0.1 to 45 wt %, 0.5 to 44 wt % or 0.75 to 43 wt %, such as 1 wt %, 1.5 wt % or 2 wt % of the chalcogenide, the halogen, or a mixture thereof, based on the total weight of the sulfur allotrope.
[0016] Amorphous chalcogenides such as sulfur shells may be the product of photon and / or electron irradiation induced ring-opening polymerization of crystalline chalcogenide allotropes.
[0017] The transition layer can be the product of photon and / or electron irradiation through a transparent graphene oxide layer coated on a crystalline allotrope of a chalcogenide, such as a sulfur core, wherein the photon and / or electron irradiation induces ROP of the chalcogenide, such as sulfur, and in situ reduction of the graphene oxide to reduced graphene oxide.
[0018] The in-situ formed transition layer can be covalently bonded to the surface of the chalcogenide active material, such as sulfur.
[0019] The transition layer can be rich in negatively charged surface functional groups (such as, but not limited to, thiols, thioethers, sulfoxides, sulfones, and sulfonic acids), resulting from photon- and / or electron-induced ROP of chalcogenides such as sulfur and deoxidation of graphene oxide to reduced graphene oxide, where the negatively charged surface acts as a polysulfide-blocking intermediate layer.
[0020] The photon / electron radiation may have a photon radiation wavelength of, for example, between 450 nm and 120 nm in terms of light / UV.
[0021] The photon / electron radiation may have a photon radiation wavelength of, for example, between 10-12 m and 10-16 m in terms of gamma radiation.
[0022] The photon / electron radiation may have an electron radiation energy of at least 5 MeV.
[0023] The covalent bonds between the transition layer comprising reduced graphene oxide and the amorphous chalcogenide, such as the sulfur shell, can be the product of providing a gaseous and / or vapor and / or liquid comonomer that optionally penetrates the inner cavity of the chalcogenide electrode. Under the action of irradiation, a chalcogenide-rich copolymer can be formed together with the transition layer comprising reduced graphene oxide.
[0024] One and / or more first coatings may be permeable to cations, such as, for example, Li+, Na+, K+, Ca2+, Zn2+, Mg2+, Al3+, but not limited thereto, and, for example, electronically conductive.
[0025] The 2D material of the first coating may be functionalized with groups capable of reacting with chalcogenides, such as sulfur, and / or decorated with metal nanoparticles, metal oxide nanoparticles, metal alloy nanoparticles, non-metal alloy nanoparticles, or mixtures of any of the above.
[0026] The electrode may be a glass and / or crystalline chalcogenide cathode, consisting of, for example, a metastable crystalline (ideally monoclinic gamma-) sulfur core. For example, the core may be stabilized by a glass / polymer / amorphous chalcogenide shell supported by a transition layer.
[0027] The transition layer may be a transition layer comprising reduced graphene oxide.
[0028] The shell may be an in-situ formed glass / polymer / amorphous shell covering the surface of the electrode material. "In-situ" may for example mean that the shell is consumed by the core.
[0029] The first coating may have a thickness of, for example, 0.3 to 500 nm, such as 5 to 500 nm, 8 to 250 nm or 10 to 200 nm, such as 1 nm, 10 nm, 100 nm, 150 nm or 200 nm, wherein the second coating may include microsheets of 2D material, nanosheets of 2D material and / or charged 2D material and / or mixtures thereof.
[0030] A second 2D material layer may be provided, for example, coating an electrode over the transition layer comprising reduced graphene oxide.
[0031] The layers may be obtained by layer-by-layer assembly, for example electrostatically driven layer-by-layer assembly, spin coating, bar coating, slot coating, roll-to-roll printing, screen printing, flexographic printing, lithographic printing, inkjet printing or film stretching.
[0032] The 2D material of the second coating layer can be selected from the group including: for example, carbon, graphene, graphene oxide, graphitic carbon nitride, hexagonal boron nitride, aluminum nitride, molybdenum nitride, titanium nitride, silicene, phosphorene, germanene, transition metal dichalcogenide, transition metal oxide, transition metal carbide, transition metal nitride or a composite mixture of any two or more of the above. For example, the second layer can include graphene and / or graphene oxide and / or a mixture of graphene oxide and reduced graphene oxide.
[0033] One and / or more second coatings may be permeable to cations, such as, but not limited to, Li+, Na+, K+, Ca2+, Zn2+, Mg2+, Al3+, and / or electronically conductive.
[0034] The second coating may have a thickness in the range of, for example, 0.3 nm to 15 μm, such as 50 nm to 15 μm, 0.5 to 14 μm, 2.5 to 13 μm, 5 to 12 μm or 7.5 to 11 μm, such as 8, 9 or 10 μm.
[0035] A portion of the second coating transition layer may be in direct contact with the electrolyte between the electrodes and / or in indirect mediated contact with a cathode electrolyte present within the electrodes.
[0036] A portion of the second coating layer may be in direct contact with the current collector.
[0037] The total thickness of the first and second coatings may range for example from 0.3 nm to 15 μm, such as 0.5 μm to 15 μm, such as 2.5 to 14 μm, 5 to 13 μm or 7.5 to 12 μm, such as 8, 9 or 10 μm, for example 10 to 200 nm.
[0038] The present disclosure further relates to a method for producing an electrode and / or a cathode, comprising at least one of the following steps:
[0039] a. providing a crystalline chalcogenide allotrope nucleus, such as a sulfur nucleus,
[0040] b. forming a first photon / electron radiation transparent coating of a material including graphene oxide on the surface of the electrode and / or cathode,
[0041] c. exposing the electrode to photon and / or electron radiation, for example, to induce ring-opening polymerization of crystalline sulfur, for example, to form an amorphous sulfur shell on a crystalline sulfur core, wherein, for example, graphene oxide is deoxidized to reduced graphene oxide by in situ reductive deoxidation through the ring-opening polymerization of crystalline sulfur induced by photon and / or electron radiation, and
[0042] d. Covalently bonding a layer comprising reduced graphene oxide to an amorphous sulfur shell.
[0043] The method may further include the step of forming covalent bonds between the transition layer comprising reduced graphene oxide and the amorphous chalcogenide shell (e.g., sulfur shell). For example, the shell may be formed by providing a gaseous and / or vapor and / or liquid comonomer, and using photon and / or electron radiation to convert the crystalline sulfur at the GO and / or sulfur interface into a sulfur-rich copolymer, and crosslinking the sulfur and / or sulfur allotrope of the electrode material with the transition layer comprising reduced graphene oxide.
[0044] The method may further comprise the step of coating the electrode with a second 2D material layer over the transition layer comprising reduced graphene oxide.
[0045] The first coating layer of step b can be formed by dip coating, vacuum filtration, spray coating, layer by layer, spin coating, bar coating, slot coating, roll-to-roll printing, screen printing, flexographic printing, lithographic printing, inkjet printing or film stretching.
[0046] The second coating may be formed by electrophoretic deposition and / or reduction of a second 2D material.
[0047] The present disclosure further relates to a primary or secondary energy storage device (eg, a battery) or an electrochemical cell, comprising, for example, an electrode as described above and / or an electrode produced according to a method as described above.
[0048] The primary or secondary energy storage device or electrochemical cell may further include, for example, at least one electrolyte, such as a liquid electrolyte, a polymer electrolyte, a gel electrolyte, a solid electrolyte, a cathode electrolyte, a composite electrolyte, and / or mixtures thereof.
[0049] In the present disclosure, the term "comprising" may mean "consisting of" or "including". | "Comprising" may mean or encompass "consisting of".
[0050] Furthermore, in the present disclosure, features combined by “ / ”, such as “glass / polymer / amorphous” may mean that at least one of the features is present, or any possible combination of the features is present.
[0051] In particular, the present disclosure relates to a structurally stable chalcogenide-rich cathode comprising glassy / amorphous / polymeric / crystalline chalcogenide allotropes, most desirably a sulfur-rich cathode, wherein one and / or more glassy / amorphous / polymeric allotropes are primarily present in the shell and one and / or more crystalline allotropes are in the core, wherein a density gradient exists between the core and the shell. Furthermore, methods for making such layers, and devices comprising such coated electrodes. More particularly, to an electrode carrying on its surface one / more layers comprising a chalcogenide-based active material, wherein more desirably sulfur and / or binary sulfur-selenium or ternary sulfur-selenium-tellurium and / or quaternary sulfur-iodine-tellurium-selenium are used as electrode active materials. Such a non-removable alkali ion and / or alkaline earth metal ion permeable coating / transition layer is induced by irradiation (i.e., gamma rays and / or accelerated electrons, or more ideally by photons below 500 nm), capable of inducing ROP of chalcogenide-based materials and generating an in-situ non-removable mixed ion / electronic transition layer by crosslinking and / or copolymerization at the interface between the active material and the transition coating. The coating consists of at least two layers, including a two-dimensional (2D) material, and is uniformly coated on the electrode surface, wherein the surface provides support for the permeable layer. This type of electrode can be used in high-energy rechargeable batteries containing alkali and / or alkaline earth metals or other electrochemical devices with cations and / or anions as charge carriers, such as, for example, Li-S batteries, Na-S batteries, Mg-S batteries, Al-S batteries, Zn-S batteries or Ca-S batteries.
[0052] Commercially, a large amount of amorphous insoluble sulfur is used in the tire vulcanization industry on a megaton scale. Such insoluble sulfur is produced, for example, by high temperature treatment and the use of end-capping agents to stabilize polymeric sulfur. In contrast, the present disclosure shows that in-situ stable insoluble sulfur allotropes can be prepared by photon / electron irradiation and stabilized by a covalently bonded mixed ion and electron permeable thin transition layer that acts as a shell. The shell protects the main crystalline chalcogenide core, more ideally the sulfur core, while allowing it to circulate, wherein the stabilizing effect is provided by a photon / electron induced thin transition layer and a process that captures glass / polymer / amorphous and crystalline chalcogenide allotropes in the desired location.
[0053] The present disclosure provides mixed alkali / ions and / or alkaline earth / ions, wherein Li + Permeable, e -A conductive non-removable protective layer is supported or carried by the surface of an electrode comprising a chalcogenide-based redox-active material. The chalcogenide-based active material and the building blocks of the subsequent one and / or multiple layers coated on the electrode in the form of a suitable precursor are treated with a suitable radiation source so that an allotropic transformation from crystalline to glassy / polymeric / amorphous is induced along with ROP. In addition, ROP is propagated within the surface of a chalcogenide cathode having a three-dimensional (3D) host, for example, a sulfur host or a monolithic sulfur wafer-like structure is introduced into a reaction with a suitable one and / or multiple comonomers in liquid and / or gaseous form and a suitable crosslinking agent / or capping agent to prevent back conversion from glassy / polymeric / amorphous sulfur back to a crystalline allotrope. In addition, the non-removable layer includes at least one two-dimensional (2D) material, namely carbon, graphene / graphene oxide, transition metal dichalcogenides (e.g., MoS2, WS2, MoTe2, MoSe2, WSe2, VS2, VS4, TiS2, TiS4, etc.), transition metal carbides / nitrides, commonly referred to as MXenes, for example, Ti2C, V2C, Mo2C, Ti3AlC2, Mo2TiC2, etc., h-BN (hexagonal boron nitride), graphitic carbon nitride (g-C3N4), or a composite mixture of any two or more thereof, and optionally, the 2D material may be decorated with metal and / or metal oxide nanoparticles. The non-removable transition layer is uniformly coated on the surface of an electrode, such as a cathode, and includes crystalline, amorphous, glassy and / or polymeric chalcogenides, most preferably sulfur, or a mixture of any two or more thereof. In some embodiments, sulfur or one or more sulfur allotropes may be doped with other chalcogenides and / or halogen dopants. Such coated electrodes (e.g., cathodes) or 3D objects can be used in high-energy rechargeable batteries containing alkali and / or alkaline earth (Li, Na, K, Ca, Mg, Al, Zn, etc.) metals / ions, such as Li-S batteries, Na-S batteries, Mg-S batteries, or Al-S, Zn-S batteries, or Ca-S batteries. Provided according to the present disclosure is an electrode (cathode) for an electrochemical device having a crystalline chalcogenide core, more ideally a sulfur allotrope core, a glass / polymer / amorphous chalcogenide shell, more ideally glass / polymer / amorphous, and a transition layer comprising reduced graphene oxide covalently bonded to the glass / polymer / amorphous chalcogenide shell.
[0054] According to the present disclosure, an electrode or cathode utilizes the beneficial properties of allotropic transformations found in chalcogenides. For example, sulfur has crystalline α, β, and γ allotropes, as well as an amorphous form. By exploiting the solubility differences between these allotropes, a transition layer is created using the least soluble allotrope. While the cycloorthorhombic α-sulfur allotrope is very soluble in carbon disulfide (CS2) solvent, the polymeric allotrope is insoluble. By constructing the transition layer from the most stable allotropic form while retaining an inner core composed of crystalline allotropes, it is possible to maximize the use of sulfur active material while alleviating the PS shuttling problem.
[0055] Ideally, the glassy / polymeric / amorphous sulfur shell is the product of photon / electron irradiation-induced ROP of crystalline chalcogenide, while the transition layer is transparent to the photon / electron irradiation, and more ideally, the transition layer is composed of graphene oxide, wherein the graphene oxide reacts with the amorphous chalcogenide, which undergoes ROP during the photon / electron irradiation and leads to in situ deoxygenation of the graphene oxide to reduced graphene oxide.
[0056] The chalcogenide-based active material and the building blocks of one or more subsequent layers in the form of suitable precursors are treated with photon / electron radiation so that an allotropic transformation from crystalline to glassy / polymeric / amorphous chalcogenide is induced along with ROP and propagates at the interface between the transition layer and the chalcogenide cathode, which may have a three-dimensional (3D) chalcogenide host, a monolithic chalcogenide wafer-like structure or the like, and is introduced into the reaction with a suitable gaseous / vaporous / liquid comonomer, penetrates into the amorphous chalcogenide shell, converts the amorphous chalcogenide shell into a chalcogenide-rich copolymer, and crosslinks between the chalcogenide / chalcogenide allotrope of the electrode material and the transition layer comprising reduced graphene oxide to form covalent bonds.
[0057] The photon / electron radiation used to induce the ring-opening polymerization is ideally blue / ultraviolet light, and / or high energy photons such as g-radiation and / or electron beams. With respect to blue / ultraviolet light, the wavelengths used in the electromagnetic spectrum should more ideally be in the range of 450 nm down to the deep UV region at 120 nm. The source of g-ray irradiation should more ideally be from 60 Co source or 137 Cs source. The electron beam energy can be between 5 and 10 MeV.
[0058] Without being bound by any particular theory, it is believed that the reaction between the coating layer comprising graphene oxide and the chalcogenide / chalcogenide allotrope in the electrode material converts the chalcogenide on the surface of the electrode material into an insoluble, stable polymer chalcogenide, thereby providing a crystalline to polymer transition between the shell and the core of the electrode / electrode material comprising the chalcogenide. In other words, the transition layer provides structural support for the electrode (e.g., cathode). This structural support helps prevent or avoid the collapse of internal pores and thereby block internal channels in the electrode material comprising sulfur, which may occur due to the volume expansion of sulfur during electrode operation.
[0059] The transition layer mitigates the PS shuttling effect during battery operation. Advantageously, the transition layer is ionically (e.g., allows alkali metal ions to pass through the layer) and / or electronically conductive. Also defined as a mixed ion and / or electronic conductor.
[0060] The sulfur in the electrode materials described herein may include any sulfur allotrope, including orthorhombic, glassy, amorphous and / or polymeric (e.g., β- and / or γ- and / or ω or other phases) sulfur, and / or a mixture of two or more sulfur allotropes, either original or doped with one or more chalcogenide dopants, halogen dopants, or any mixture of two or more of the above, such as doped with selenium (Se), tellurium (Te), iodine (I), or any mixture of two or more thereof. The electrode material may also include further chalcogenide-based redox active materials, such as Se, Te, or mixtures thereof. The structure of the electrode material is not particularly limited, and may be a three-dimensional (3D) bulk or wafer-like structure.
[0061] Ideally, the doped sulfur allotrope included in the electrode material may include, based on the total weight of the sulfur allotrope, from 0.001 to 50 wt % of a chalcogenide (e.g., Se and / or Te), a halogen, or a mixture thereof other than sulfur, such as 0.01 to 49 wt %, 0.1 to 45 wt %, 0.5 to 44 wt % or 0.75 to 43 wt %, such as 1 wt %, 1.5 wt % or 2 wt % of a chalcogenide (e.g., Se and / or Te), a halogen, or a mixture thereof.
[0062] Ideally, the transition layer comprising reduced graphene oxide covalently bonded to the amorphous sulfur shell is a mixed alkali / ion and / or alkaline earth / ion and more preferably Li + Permeable, e - A conductive, non-detachable, protective two-dimensional (2D) material layer is supported or carried by the outer surface of a sulfur electrode including a chalcogenide-based redox-active material.
[0063] In addition, the reduced graphene oxide, non-detachable two-dimensional (2D) material layer may also include carbon, graphene / graphene oxide, transition metal dichalcogenides (e.g., MoS2, WS2, MoTe2, MoSe2, WSe2, VS2, VS4, TiS2, TiS4, etc.), transition metal carbides / nitrides, commonly referred to as Mxene, for example, Ti2C, V2C, Mo2C, Ti3AlC2, Mo2TiC2, etc., h-BN, graphitic carbon nitride (g-C3N4), or a composite mixture of any two or more thereof.
[0064] In addition, the 2D material can be decorated with metal and / or metal oxide nanoparticles. The 2D material can be doped and / or functionalized with one or more functional groups. Examples of functional groups include =O, -OH, -COOH, -F, -COO, -NO3, -NO2, -R, -Cl, -NH.
[0065] Ideally, the non-removable, transitional, two-dimensional (2D) material layer is uniformly coated on the surface of the electrode or cathode and may have a thickness of 2nm to 15μm, such as 5nm to 10μm, 8nm to 5μm or 10nm to 1μm, such as 10nm, 15nm or 20nm.
[0066] The coated electrodes or cathodes described herein can include 1 to 99 wt % chalcogenide, ideally sulfur, such as 20 to 98 wt %, 30 to 97 wt %, 40 to 96 wt %, 50 to 95 wt %, 60 to 94 wt %, 70 to 93 wt %, or 80 to 92 wt % sulfur, such as 80, 85, 86, 87, 88, 89, or 90 wt % sulfur, based on the total weight of the coated electrode.
[0067] The overall structure of the electrode material may have the form of a porous monolithic sulfur wafer, for example, an independent monolithic polycrystalline sulfur wafer comprising twin and / or branched nanocrystals of monoclinic sulfur, such as the porous monolithic sulfur wafer disclosed in WO 2021 / 233965A1. It is particularly advantageous to have a crystal-to-polymer transition between the core and the shell of the sulfur-containing electrode / electrode material (cathode). It is also desirable that the structure of the core may have a lower density and a tailored porosity, for example, as present in monoclinic crystalline sulfur.
[0068] In a further preferred embodiment, the electrode (cathode) according to the present disclosure may have a second 2D material layer, coating the electrode on top of the transition layer comprising reduced graphene oxide.
[0069] The 2D materials of the coated first and second layers may be microsheets, nanosheets, nanoflakes, nanoplatelets or mixtures thereof.
[0070] The first and second coatings are also permeable to cations such as Li + 、Na + , Ca 2+ Mg 2+ 、Al 3+ and Zn 2+ , and is electronically conductive. The combined thickness of the first and second coatings may be from 5 nm to 15 μm, with the first coating ideally having a lower density than the second coating.
[0071] The first and second coatings desirably form a protective transition coating on the surface of the chalcogenide-containing electrode / electrode material. The second layer is deposited / coated on the first inner coating and in intimate contact with the first coating, covering the entire surface of the first layer.
[0072] It is further advantageous when the 2D material coating is transparent to photons passing through the thickness of the electrode.The first and / or second 2D material coating may further be volumetrically flexible.
[0073] The 2D material can, for example, be selected from the group consisting of carbon, graphene, graphene oxide, graphitic carbon nitride, hexagonal boron nitride, aluminum nitride, molybdenum nitride, titanium nitride, silicene, phosphorene, germanene, transition metal dichalcogenides, transition metal oxides, transition metal carbides, transition metal nitrides, or a composite mixture of any two or more of the foregoing.
[0074] Each of the first and second coating layers may consist of a single layer, the first coating layer may consist of a single layer and the second coating layer may have a laminated structure, the first coating layer may have a laminated structure and the second coating layer may consist of a single layer, or each of the first and second coating layers may have a laminated structure.
[0075] As used herein, the term "laminate" refers to an assembly comprising two or more layers of material, such as two or more stacked layers. In general, a laminate can be considered a plate or thin shell structure, which is usually formed by building up successive layers of material. Layers of different materials can be used, thereby forming a hybrid laminate. Laminates can provide desired engineering properties, including in-plane stiffness, bending stiffness, strength, and thermal expansion coefficient.
[0076] If present, the first and second coatings may include, based on the total weight of the coated electrode, 0.1 to 30 wt % charged 2D material, such as 1 to 25 wt %, 2 to 20 wt %, 3 to 15 wt % or 4 to 12 wt % charged 2D material, such as 8.5 wt %, 9 wt % or 10 wt % charged 2D material.
[0077] The transition and allotrope stabilizing layer, i.e., the combination of the first and second coatings described herein, can improve the stability of the electrode during expansion / contraction, i.e., during battery discharge / charge, and ensure maximum utilization of the active material of the electrode because it forms a stable structure with the chalcogenide / chalcogenide allotrope contained in the electrode material.
[0078] The coated electrodes / cathodes according to the present disclosure allow for a new electrode design, namely "fish-scale design". Unlike the most advanced methods, the covalently bonded, non-removable protective transition first layer creates a strong and effective contact between the electrode (e.g., cathode) structure including chalcogenides, more ideally sulfur, and the electrolyte (e.g., cathode electrolyte), thereby achieving superior and stable ion and / or electron transport. Therefore, the coated electrodes disclosed herein reduce or overcome the low conductivity problem of chalcogenides, more ideally sulfur and polysulfide shuttles, ensuring sufficient ion and electron conduction pathways and high utilization of electrode (e.g., cathode) materials during the cycle process.
[0079] Overall, the described technology has great potential for improving and mass-producing advanced electrodes, such as cathodes, for energy storage devices with improved performance.
[0080] In addition, a method for producing an electrode (cathode) comprising a crystalline sulfur allotrope core and a photon / electron transparent transition layer is provided. Preferably, photon / electron irradiation causes in-situ reduction of graphene oxide, resulting in the formation of rGO and ROP of crystalline sulfur, and forming a glass / polymer / amorphous sulfur-rich shell on the crystalline sulfur core, wherein the graphene oxide reacts with the active sulfur to form reduced graphene oxide, thereby covalently bonding the layer comprising reduced graphene oxide to the glass / polymer / amorphous sulfur shell.
[0081] As with the above-described electrodes, the step of generating covalent bonds between the transition layer comprising reduced graphene oxide and the glass / polymer / amorphous sulfur shell is ideally performed by providing a gaseous / vapor / liquid comonomer that penetrates into the amorphous sulfur shell, converts the amorphous sulfur shell into a sulfur-rich copolymer, and crosslinks the sulfur / sulfur allotrope of the electrode material with the transition layer comprising reduced graphene oxide, forming covalent bonds between the first transition layer and the sulfur of the electrode material, thereby rendering the coating non-detachable.
[0082] Furthermore, the method may comprise the step of coating the electrode with a second 2D material layer over the transition layer comprising reduced graphene oxide.
[0083] The application of the coatings can be performed, for example, by dip coating or electrostatically driven layer-by-layer (LbL) assembly of the materials. Covalent bonding of the first coating or transition coating, i.e., the first and second coating, to the chalcogenide surface of the electrode material can be provided by triggering the ring-opening polymerization of the chalcogenide driven by photons of a certain frequency and / or electrons accelerated to a certain speed.
[0084] The present disclosure provides a solution to one or more key problems associated with existing chalcogenide-based alkali / alkaline earth metal / ion (MX) batteries (where M = Li, Na, Mg, Al, Ca, K, Zn, etc., and X = S, Se, Te and / or mixtures thereof) because it integrates the beneficial properties of crystalline and amorphous chalcogenide electrode (e.g., cathode) materials such as sulfur by providing an electrode material coated with a thin, covalently bonded, insoluble copolymer "shell" layer that protects the "crystalline core" structure of the electrode material.
[0085] According to the present disclosure, the electrode or cathode provides improved electronic and / or ionic conductivity because reduced graphene oxide (rGO) is a good electrical conductor and is able to mechanically buffer any volume changes while physically / chemically mitigating polysulfide dissolution during cycling.
[0086] The electrode can be used in an electrochemical energy storage device, such as a primary and / or secondary rechargeable battery containing alkali and / or alkaline earth (Li, Na, K, Ca, Mg, Al, Zn, etc.) and / or Al metal / ions, for example, a high-energy Li-S battery, a Na-S battery, a Mg-S battery or an Al-S battery, and / or similar electrochemical devices.
[0087] Examples of energy storage devices include, for example, electrochemical energy storage devices or primary and / or secondary rechargeable batteries containing alkali and / or alkaline earth (Li, Na, K, Ca, Mg, Al, Zn, etc.) metals / ions, such as, for example, Li-S batteries, Na-S batteries, Mg-S batteries, or Al-S batteries.
[0088] In a preferred embodiment, the energy storage device may be a lithium ion or lithium-sulfur battery, in particular a lithium-sulfur battery.Within the scope of the present disclosure, the coated electrode (eg cathode) may not contain any (additional) current collector, or may include an additional separate current collector.
[0089] Electrochemical devices including coated electrodes according to the present disclosure provide advantages such as, for example, stable and longer cycle life and rate performance due to the transition layer interface between the electrode and the electrolyte. The transition layer not only prevents electrode (cathode) degradation and disintegration, but also improves performance. Thus, the storage devices described herein can, for example, provide better electronic and / or ionic conductivity, improve active material utilization, advantageously buffer any volume changes, and mitigate polysulfide dissolution during cycling.
[0090] The primary or secondary energy storage device or electrochemical cell may further include at least one electrolyte, such as a liquid electrolyte, a polymer electrolyte, a solid electrolyte, or a mixture thereof. Typically, the primary or secondary energy storage device or electrochemical cell requires alkali and / or alkaline earth metals (Li, Na, K, Ca, Mg, Zn, Ca, Al, etc.), Al metal / ions, graphite, Si, Ge, LTO, Sn, sulfurized polyacrylonitrile (SPAN) structures, or a mixture of any two or all thereof for charge / discharge cycles.
[0091] It is further generally preferred that the primary or secondary energy storage device or electrochemical cell may include an alkali metal, alkaline earth metal, aluminum metal or a metal alloy as an anode and a porous separator disposed between the cathode and the anode.
[0092] Further examples of the present disclosure are described below:
[0093] In a further example, the present disclosure may be directed to a coated electrode comprising:
[0094] (a) a porous sulfur-based active electrode material comprising a core containing at least one crystalline and / or amorphous sulfur allotrope,
[0095] (b) a transition layer covering the surface of the active electrode material, the transition layer comprising:
[0096] (i) Two-dimensional (2D) materials;
[0097] (ii) covalent bonding between the 2D material and the sulfur of the electrode material; and
[0098] (iii) 12 wt% or less of polymeric sulfur, based on the total weight of the coated electrode;
[0099] as well as
[0100] (c) A coating layer on top of the transition layer, the coating layer comprising a 2D material.
[0101] In a further example, the present disclosure may be directed to a method of producing a coated electrode, comprising the steps of:
[0102] (a) providing a free-standing porous sulfur-based electrode structure comprising a crystalline sulfur allotrope core as a substrate;
[0103] (b) applying a continuous coating comprising a two-dimensional (2D) material on the surface of a sulfur-based electrode substrate;
[0104] (c) forming a transition layer, including covalent bonds between the 2D material of the coating and the sulfur of the sulfur-based electrode substrate, and polymeric sulfur at the interface between the coating and the substrate;
[0105] (d) Applying a coating comprising a second 2D material on the transition layer.
[0106] Further elements and advantages of the present disclosure can be obtained from the following figures and description of preferred embodiments. The figures show: BRIEF DESCRIPTION OF THE DRAWINGS
[0107] Figure 1 Schematic diagram of an example of process steps for forming a first continuous coating including a two-dimensional (2D) material on a porous chalcogenide wafer substrate;
[0108] Figure 2 Schematic diagram of an embodiment of a process step for forming covalent bonds between a first coating of 2D material and a sulfur substrate by irradiating a coated chalcogenide wafer;
[0109] Figure 3 A schematic diagram of an embodiment of a process step for forming a second coating layer including a second 2D material on a first coating layer;
[0110] Figure 4 Photograph of a grown 3D sulfur wafer substrate electrode material (e.g., cathode) fabricated as described in WO 2021 / 233965 A1;
[0111] Figure 5A A flow chart of an example of a method for producing a coated electrode;
[0112] Figure 5B A flow chart of another example of a method for producing a coated electrode;
[0113] Figure 6 Schematic diagram (cross section) of an example of a protective layer coating electrode material according to an embodiment of the present disclosure;
[0114] Fig. 7A , Figure 7B and Figure 7C Illustrative examples of embodiments of coated battery electrodes (70) according to the present disclosure;
[0115] Figure 8 Schematic depiction of the interaction of lithium ions with an embodiment of a coated electrode according to the present disclosure;
[0116] Fig. 9 It is a powder X-ray diffraction (p-XRD) pattern of an embodiment of a coated electrode according to the present disclosure. The coated electrode includes a porous sulfur wafer substrate as disclosed in WO2021 / 233965A1 and a first GO coating formed by dip coating (i.e., immersing an independent porous sulfur wafer in a GO dispersion and then drying) and covalently bonded to the sulfur of the electrode material by irradiation treatment. The coated electrode also includes a second GO coating on top of the first covalently bonded GO / r-GO coating, which is thicker than the first coating and is formed by electrophoretic deposition coating. The diffraction pattern was collected by X-ray powder diffraction measurements on a STOE Stadi MP diffractometer equipped with a Dectris Mythen 1K linear silicon strip detector and a Ge (111) double crystal monochromator (Mo Kα1 radiation) in transmission geometry.
[0117] The existence of monoclinic beta (β) sulfur allotrope was confirmed.
[0118] Fig. 10A and 10B The results of a study of the galvanostatic charge / discharge behavior and cycling performance of the pristine sulfur wafer cathode at C / 10 according to WO 2021 / 233965 A1 are shown. Fig. 10C and 10D Results of studies of the galvanostatic charge / discharge behavior and cycling performance of embodiments of coated electrodes according to the present disclosure, i.e., GO-coated and irradiated sulfur wafer cathodes, at C / 10 are shown. For the cell, 1 M LiTFSI and 0.1 M LiNO3 in DOL / DME (1:1) were used as electrolytes. By comparing the charge and discharge behavior of the original sulfur wafer and the sulfur wafer after GO coating and irradiation, it can be clearly seen that the latter cathode performs better than the original sulfur wafer in terms of initial utilization factor and capacity retention. This is due to the enhanced electronic conductivity of the treated sulfur wafer, which leads to the reduction of GO after irradiation and cross-linking with the sulfur active material, which is beneficial to the capacity retention of the cathode.
[0119] Cycling measurements were performed on a LAND cycler in galvanostatic mode using metallic lithium, cellgrad 2500 separator and ether electrolyte with the provided LAND software (version 7.4).
[0120] Reference numerals list
[0121] 10 Process steps for forming the first continuous coating
[0122] 11. Porous sulfur wafer substrate
[0123] 12 Dispersion
[0124] 13 Coating / Coated Sulfur Wafers
[0125] 20 Process steps for forming covalent bonds
[0126] 21 Oxygen-sulfur bond
[0127] 30 EDP process
[0128] 31 Positively charged dispersion
[0129] 32 Negatively charged dispersion
[0130] Chamber 33 / 34
[0131] 60 Coated Electrode
[0132] 61 Electrolytes
[0133] 62 Second coating
[0134] 63 First coating
[0135] 64 Porous sulfur substrate
[0136] 65 current collector
[0137] 70 Coated battery electrodes
[0138] 71 Current collector tab
[0139] 72 protective layer
[0140] 80 Coated Electrode
[0141] 81 Lithium Ion
[0142] 82 Second coating
[0143] 83 First coating
[0144] 84 Porous sulfur substrate DETAILED DESCRIPTION
[0145] In one aspect of the present disclosure, there is provided a coated electrode, comprising:
[0146] (a) Chalcogenides, more preferably sulfur, as electrode materials;
[0147] (b) a first coating layer comprising a two-dimensional (2D) material and covering the entire surface of the electrode; and
[0148] (c) a second coating layer on top of the first coating layer, the second coating layer comprising a 2D material; wherein the first coating layer is covalently bonded to the chalcogenide-based electrode material.
[0149] The inventors have found that coated electrodes according to the present disclosure provide improved electronic and / or ionic conductivity, are able to buffer any volume changes, and mitigate polysulfide dissolution during cycling. In particular, it was found that electrodes comprising 2D materials coated with ionically and electronically conductive, covalently bonded protective layers as described herein provide stable cycling performance and significantly improved galvanostatic charge / discharge behavior.
[0150] The inventors have discovered that the coated electrodes according to the present disclosure allow for a new electrode design, namely a "fish scale design". In one embodiment, the coated electrode can be a cathode with a "fish scale design". Unlike current process methods, the covalently bonded, non-removable protective layer creates a strong and effective contact between the electrode (e.g., cathode) structure including sulfur and the electrolyte (e.g., cathode electrolyte), thereby achieving superior and stable ion and / or electron transport. Therefore, the coated electrodes disclosed herein reduce or overcome the problems of low conductivity, polysulfide shuttling, and active material utilization of current electrodes because the electrode / current collector design disclosed herein ensures sufficient ion and electron conduction pathways and high utilization of electrode (e.g., cathode) materials during the cycle. In general, the technology has great potential in the rational improvement and large-scale production of advanced electrodes such as cathodes for energy storage devices with improved performance.
[0151] The present disclosure provides a non-detachable transition layer supported or loaded by the surface of an electrode (e.g., a cathode) including sulfur as an electrode material. The sulfur in the electrode material described herein may include any sulfur allotrope, original or doped with one or more chalcogenide dopants, halogen dopants, or any mixture of two or more of the above, such as doped with selenium (Se), tellurium (Te), iodine (I), or any mixture of two or more of them. The electrode material may also include further chalcogenide-based redox active materials, such as Se, Te, or mixtures thereof. The structure of the electrode material is not particularly limited, and may be a three-dimensional (3D) body or a wafer-like structure.
[0152] In addition, the transition layer, i.e., the combination of the first and second coatings described herein, can improve the stability of the electrode during expansion and ensure that the active material of the electrode is maximized because it forms a stable structure with the sulfur / sulfur allotrope contained in the electrode material. In particular, without being bound by any particular theory, it is believed that the reaction between the 2D material of the coating and the sulfur / sulfur allotrope in the electrode material converts the sulfur on the surface of the electrode material into insoluble, stable glass / polymer / amorphous sulfur, thereby providing a crystalline to polymer transition between the core and shell of the electrode / electrode material containing sulfur.
[0153] In other words, the transition layer provides structural support for the electrode (e.g., cathode, including sulfur wafers). This structural support helps prevent or avoid collapse of internal pores and thereby blockage of internal channels in the electrode material containing sulfur, which may occur due to volume expansion of sulfur during electrode operation. According to the preferences generally applicable in the context of the present disclosure, the transition layer mitigates the polysulfide shuttling effect during cell operation. Advantageously, the transition layer is ionically (e.g., allows alkali metal ions to pass through the layer) and / or electronically conductive. The transition layer may include more than two sublayers.
[0154] In a preferred embodiment, the transition layer comprises a first inner coating layer and a second outer coating layer, wherein the inner coating layer is in direct contact with and cross-linked (covalently bonded) with the active material of the electrode (e.g., cathode) comprising or consisting of sulfur / sulfur allotropes. In one embodiment, the ionically and electronically conductive protective layer has a thickness between 5 nm and several micrometers, for example, 5 nm to 15 μm, such as, for example, 10 μm.
[0155] In one embodiment, one side of the second outer coating is in direct contact with the electrolyte (e.g., cathode electrolyte), while the other side may be in direct contact with the current collector (see, e.g., Figure 6 ). The protective layer includes, for example, nanosheets of 2D material, which may further be positively charged or negatively charged.
[0156] In a preferred embodiment, the protective layer has a density gradient that may include GO / r-GO. The conductive transition layer described herein has a beneficial effect on battery performance, such as cycling and rate response. For example, such a transition layer can reduce interfacial resistance and minimize or eliminate delamination or cracking and loss of active material of the electrode (e.g., cathode), thereby resulting in an increase in life.
[0157] Typically, 2D materials include or are made of: carbonaceous materials, non-carbonaceous materials, or mixtures thereof. For example, 2D materials include or can be made of: carbon; metals such as aluminum (Al), bismuth (Bi), boron (B), copper (Cu), gallium (Ga), germanium (Ge), indium (In), iron (Fe), gold (Au), molybdenum (Mo), platinum (Pt), ruthenium (Ru), silicon (Si), silver (Ag), selenium (Se), tin (Sn), titanium (Ti), tellurium (Te), tungsten (W), vanadium (V), and zinc (Zn), or oxides and alloys thereof; transition metal dichalcogenides, such as Such as MoS2, WS2, VS2, VS4, TiS2 and TiS4; transition metal carbides (MXene), such as Ti2C, V2C, Mo2C, Ti3AlC2 and Mo2TiC2; transition metal nitrides / carbonitrides, such as graphitic carbon nitride (g-C3N4), hexagonal boron nitride (h-BN), silicene, phosphorene, germanene, boron-carbon-nitrogen (BCN), aluminum nitride, molybdenum nitride, titanium nitride and their alloys; or a composite mixture of any of the above.
[0158] 2D materials can be doped and / or functionalized with one or more functional groups. Examples of functional groups include -O, -OH, -COOH, -F, -COO, -NO3, -NO2, -R, -Cl, -NH.
[0159] The 2D material may be a microsheet, a nanosheet, a nanolayer, a nanosheet, or a mixture thereof, ideally a microsheet or a nanosheet, such as, for example, a microsheet or a nanosheet of graphene, graphene oxide (GO), reduced graphene oxide (r-GO), MXene, g-C3N4, h-BN, silicene, phosphorene, germanene, BCN, a transition metal dichalcogenide, or a mixture of two or more of the foregoing. Within the scope of one embodiment, the 2D material is a microsheet or a nanosheet. In the context of the present disclosure, typically, preferred 2D materials include, for example, GO, MoS2, Ti2C, Ti4O7 (Magnelli phase titanium dioxide), h-BN, and mixtures of graphene and GO, GO and MoS2, MoS2 and Ti2C, and GO and h-BN. According to preferences generally applicable in the context of the present disclosure, the 2D material comprises nanosheets of graphene oxide (GO) and / or nanosheets of graphene, GO, reduced graphene oxide (r-GO) or mixtures thereof, such as, for example, GO / r-GO.
[0160] According to the generally applicable preferences within the scope of the present disclosure, the electrode (e.g., cathode) material can be sulfur and / or sulfur allotropes, including orthorhombic, glassy, amorphous and / or polymer (e.g., β- and / or γ- and / or ω-phase) sulfur, and / or a mixture of two or more sulfur allotropes. Examples of sulfur / sulfur allotropes include cyclic sulfur, amorphous chain sulfur, tad-pole photo sulfur allotropes, copolymerized sulfur doped with other chalcogenides and / or halogen dopants, carbon-sulfur composites including carbon allotropes or defective carbonaceous structures with sulfur and / or other sulfur allotropes, or other sulfide electrode materials. Typically, the electrode is a 3D body including crystalline, amorphous or polymer (e.g., β- and / or γ- and / or glassy / polymer / amorphous) sulfur or a mixture thereof.
[0161] Figure 1 Schematic diagram of an example of a process step for forming a first continuous coating comprising a two-dimensional (2D) material on a porous sulfur wafer substrate as disclosed in WO 2021 / 233965 A1 by dip coating. The porous sulfur wafer substrate (11) is immersed in a dispersion (12) of the 2D material, wherein the 2D material is electrostatically attached to the surface of the substrate electrode (e.g., cathode) structure. After removing the substrate and drying it, a porous sulfur wafer substrate having a first continuous coating (13) is obtained. The coating steps (i.e., dipping, floating, and drying) can be repeated several times until the desired first coating thickness is reached. In one embodiment, the 2D material can be graphene oxide (GO), and therefore, the process step can result in the electrode (cathode) being coated with a thin (e.g., 5-500 nm thick) graphene oxide (GO) layer covering the entire surface of the electrode material.
[0162] An example of a dip coating process is shown in Figure 1 For example, the dip coating process may include providing a dispersion (12) or suspension of a certain amount of the 2D material to be coated in a liquid medium comprising water, ethanol, methanol, acetone, IPA, DMF, NMP, DMSO and / or mixtures thereof, with or without the aid of a suitable surfactant, such as, for example, SDS, SDBS, CTAB, Triton X-100, etc., and / or mixtures thereof, followed by sonication, ultrasound treatment and / or centrifugation. As previously mentioned, the 2D material may include positively charged and / or negatively charged 2D materials.
[0163] The formation of the first coating layer can be achieved by electrostatically driven layer-by-layer (LbL) assembly, i.e., dip coating / drying or spray coating / drying, such as, for example, by placing the electrode material (11) including sulfur in a suitable dispersion (12) for a few minutes and then drying with, for example, IR, air, etc., as Figure 1As shown. The process of LbL coating, i.e., dipping, floating and drying, can be repeated as needed until the desired thickness of the first coating layer such as described above is reached. In the context of the present disclosure, 2D material nanosheets are generally preferred for forming the first coating layer. According to the preferences generally applicable in the context of the present disclosure, the first coating layer may include at least graphene oxide (GO) as the 2D material, which can be applied to the sulfur substrate by electrostatically attaching the GO nanosheets to the surface of the electrode material using the LbL coating process.
[0164] According to a generally preferred embodiment, the first coating layer can be formed in a thickness range of 2 to 450 nm, such as 5 to 350 nm, 8 to 250 nm or 10 to 200 nm, such as 10 nm, 50 nm, 100 nm, 150 nm or 200 nm. In the context of the present disclosure, it is generally preferred when the first coating layer is thinner than the second coating layer.
[0165] The method for preparing a coated electrode further includes a step of forming a covalent bond between the 2D material of the first coating and the sulfur substrate of the electrode material. This step of forming a covalent bond (503) is performed using a surface-driven ROP of a chalcogenide. The ROP can be induced, for example, by irradiation, such as by flash lamp annealing (FLA), UV, VUV, electron beam or gamma irradiation, or a combination of two or more of the above. Typically, the irradiation dose ranges from 1 kGy to 300 kGy, such as 10-100 kGy, or for example 80 kGy, to induce crosslinking between the chalcogenide / chalcogenide allotrope of the electrode material and the 2D coating material such as, for example, GO nanosheets. In the report, where the surface-driven photon-induced ROP of sulfur is described, a suitable gaseous and / or vapor comonomer that can only penetrate a shallow depth of the 3D sulfur host is utilized to convert the shell of the 3D sulfur host into a sulfur-rich copolymer, while the core retains its crystalline structure. This chalcogenide-rich copolymer at the interface is referred to as a "fish scale" structure, and the photon and / or electron radiation-induced process reportedly uses an average of 82 to 95 wt.% sulfur, and converts at least 3 to 12% of the sulfur into the copolymer by reaction with 2 to 6 wt.% of (one or more) gaseous, vapor and / or liquid comonomers. Due to the crosslinking (i.e., formation of covalent bonds or short sequences of bonds) between the chalcogenide / chalcogenide allotrope of the electrode material and the 2D coating material contained in the first coating, the first coating becomes an integral, non-detachable part of the electrode.
[0166] At least the first coating formed on the sulfur substrate is transparent or semi-transparent to high-energy radiation, ultraviolet light and / or electron beams such as high-energy electron beams, so that the activation / ring-opening polymerization (ROP) of the chalcogenide can be triggered by a photon / electron source at a specific frequency / energy, where most of the spectrum is not absorbed by the layer and reaches the chalcogenide / chalcogenide allotrope contained in the electrode material.
[0167] The first coating includes a 2D material and / or a composite thereof capable of directly or indirectly mediating a reaction with sulfur. In general, without being bound by any particular theory, it is believed that ROP is a process in which the ends of cyclic sulfur monomers are opened to form linear sulfur S x ● A free radical process is described, and the reaction propagates from the internal sulfur core to the first coating layer applied thereon, wherein the sulfur radical species simultaneously react with a suitable 2D material contained in the first coating layer deposited on the surface of the electrode material including sulfur / sulfur allotropes.
[0168] Figure 2 is a schematic diagram of an embodiment of a process step for forming covalent bonds between a 2D material of a first coating and a sulfur substrate by irradiating a coated sulfur wafer (13) according to an embodiment of the present disclosure. The interface region in the figure is idealized. Irradiation induces crosslinking between the sulfur substrate electrode material and one or more 2D coating materials, for example, oxygen-sulfur bonds (21) are formed between sulfur on the surface of the electrode substrate material and a coating comprising graphene oxide (GO) nanosheets by irradiation-induced ring-opening polymerization (ROP). In embodiments where the electrode material is coated with a thin layer of GO, the ROP reaction begins with photon-induced ring opening of sulfur within the core, which propagates toward the coating (protective / transition shell) where it reacts with and reduces GO to produce partially reduced graphene oxide (r-GO).
[0169] exist Figure 2 In the exemplary embodiment shown, the FLA device is used for ROP. Typically, the effective wavelength can be in the blue to UV range (100-400nm), because the photon energy in this range is sufficient to trigger the ROP reaction. In order to induce non-thermal ROP, photons at suitable energy and frequency, i.e., gamma and / or UV range and / or electrons, are required. Alternatively, thermally induced ROP can be used, for example, using a laser source, such as an infrared (IR) laser, to induce ROP by simultaneously raising the temperature to greater than 159°C, more ideally around 185°C by local heating. Typically, the irradiation process is carried out in a protective environment. Due to irradiation, sulfur becomes insoluble in most solvents by converting α, β and γ sulfur allotropes into polymer chain sulfur. Therefore, coating with a 2D material such as GO and then irradiating can convert soluble α, β and γ sulfur into insoluble stable polymer sulfur.
[0170] In a generally preferred embodiment, the first coating layer may include GO, and thus the ROP process may include the following: sulfur radicals with unpaired electrons at both ends of the chain are formed by photon-induced intracore sulfur polymerization / fragmentation, and then propagate toward the first coating layer including GO, where these sulfur radicals react with GO and partially reduce it to r-GO, i.e., deoxy GO, while maintaining attachment of specific negatively charged functional groups. In other words, the sulfur radicals act as an in-situ reducing agent for GO. An example of a typical result of the reduction reaction of GO to r-GO with sulfur radicals is shown below:
[0171]
[0172] As shown above, due to the weak reducing power, residual carboxyl functional groups may be left on GO. In particular, the materials produced by the ROP process have the following characteristics:
[0173] Partially recovered graphite network-basal plane;
[0174] Restored conductivity of r-GO (>100S / cm)
[0175] The presence of S functional groups, such as, for example, sulfinyl (>SO), sulfone;
[0176] Sulfoxide Thiols, thioethers, thiosulfonates and sulfonic acid Functional groups are distributed on the edge or surface of the covalently bound first coating 2D material, such as, for example, GO / r-Go.
[0177] Negatively charged functional groups attached to 2D materials, such as GO / r-GO, can then be used as suitable dopants in subsequent processes. These negatively charged functional groups on the surface can participate in reactions with suitable comonomers and can also provide doping for conjugated polymers such as poly (3,4-ethylenedioxythiophene) (PEDOT). The presence of highly thermally conductive r-GO (thermal conductivity ~800 W / mK) on the surface, as well as low thermal conductivity sulfur (~0.12 W / mK), can allow the formation of a thermal gradient between the electrode material core and the coating shell structure. The results show that the preferred growth of the monoclinic sulfur allotrope can propagate from the outer (shell) to the inner (core) direction during the annealing process, thereby enabling the formation of a structure with a density gradient between the core and the shell due to crystallization. In addition, the electrode material including sulfur can provide support for UV transparent and / or semi-transparent first and / or second coatings including 2D materials such as graphene oxide (GO), while the covalently bound layer can be able to provide structural support for electrode materials such as, for example, sulfur wafers. In cases where the photon irradiation intensity exceeds the melting point of sulfur and there is a risk of structural collapse and closure of internal pores, a first coating including a 2D material such as GO can provide structural reinforcement.
[0178] Figure 3 is a schematic diagram of an embodiment of a process step for forming a second coating layer including a second 2D material on a first coating layer according to the present disclosure.
[0179] The step of forming a second coating (504 or 505 (i)) is not particularly limited and includes methods generally known to those skilled in the art for applying a coating on a surface. For example, the second coating can be applied to a first coating supported by an electrode material comprising sulfur / sulfur allotropes by an electrophoretic deposition (EPD) process. EPD is a technique in which charged particles in a stable colloidal suspension are transported through a liquid and deposited on a conductive substrate with opposite charge due to the presence of an electric field. The EPD process enables film coatings with a wide range of thicknesses from a few nanometers to a few microns, and structures from porous to highly compact, which are easy to control. Films deposited / coated using the EPD process can include different compositions or concentration gradients and can be formed in a relatively short time. Typically, the EDP process is performed in a monopolar and / or bipolar battery. It is generally preferred that the second coating is thicker than the first coating. It is also preferred within the scope of the present disclosure when the second coating is also transparent or translucent, for example, to ultraviolet light and / or electron beams, such as high-energy electron beams.
[0180] An example of an EDP process (30) using a bipolar battery is Figure 3As shown. The bipolar battery in this example includes a cathode electrolyte flow of a positively charged dispersion (31) containing a second 2D material through a chamber (33), an anode electrolyte flow of a negatively charged dispersion (32) containing a second 2D material through a chamber (34), and a porous sulfur wafer substrate having a first coating located between the cathode electrolyte flow through the chamber (33) and the anode electrolyte flow through the chamber (34). In one embodiment, the 2D material for the second coating can include GO, and thus, the EDP treatment can provide a second thicker (e.g., 50nm-15μm thick) GO coating on top of the first thin coating that is covalently bonded to sulfur on the surface of the electrode material. For example, the chambers (33, 34) of the bipolar battery can be filled with an anode electrolyte (electrolyte solution containing anionic substances) and a cathode electrolyte (electrolyte solution containing cationic substances) solution including a positively / negatively charged 2D material such as graphene / graphene oxide nanosheets. The flow of each solution through the chamber can be controlled and maintained. An electrode material comprising sulfur / sulfur allotrope and a first coating (13 / 21), such as, for example, a sulfur wafer with a first coating, can be placed between two chambers of a bipolar battery so that an anolyte and a catholyte solution can reach the electrode material. Deposition of a positively / negatively charged 2D material (such as, for example, graphene / graphene oxide nanosheets) can then be performed by applying a suitable potential of 0.1-600 V (such as, for example, 10 V, 20 V or higher) between the chambers of the bipolar battery, while maintaining / controlling the concentration and flow rate of the anolyte and catholyte solutions in the respective chambers ( Figure 3 ). As a result, a thick layer of positively / negatively charged 2D material nanosheets is coated on the electrode material, and an electrode with a protective layer as described herein can be obtained, e.g. Figure 6 Schematically shown in .
[0181] exist Figure 6 In the embodiment of the electrode shown in the corresponding figure, the ion- and electron-conducting protective layer has a thickness between 5 nm and several micrometers, for example, 5 nm to 15 μm, such as, for example, 10 μm. One side of the second outer coating is in direct contact with the electrolyte (e.g., cathode electrolyte), while the other side can be in direct contact with the current collector (see, for example, Figure 6 ). The protective layer includes, for example, nanosheets of 2D material, which may further be positively charged or negatively charged.
[0182] The conductive protective layer described herein has a beneficial effect on battery performance, such as cycling and rate response. Such a protective layer can reduce interfacial resistance and minimize or eliminate delamination or cracking and loss of active material of the electrode (e.g., cathode), thereby leading to an increase in life.
[0183] Figure 4 is a photograph of a grown 3D sulfur wafer substrate electrode material (e.g., cathode) fabricated as described in WO 2021 / 233965 A1.
[0184] In general, porous sulfur substrates that can be used as electrode materials, such as lithium-sulfur batteries, can be made using four different methods. These methods depend on the electrode material used, such as the cathode material. The first method involves the use of sulfur in a charged state, while the second method involves the use of Li2S in a discharged state. The third method uses a sulfur-rich cathode electrolyte, and the fourth method uses covalently bonded sulfur. In the present disclosure, a combination of the first, fourth, and part of the second method is used, which provides several benefits. Li2S-based electrodes such as cathodes exhibit the lowest density in the discharged state and therefore occupy the largest volume in the electrode (expanded state). In addition, the internal porosity or voids in the electrode (cathode) are minimized. This characteristic of the electrode (cathode) determines the overall performance of the battery, such as a lithium-sulfur battery. Any suitable porous sulfur substrate can be provided as an electrode material, including an electrode material comprising or consisting of: sulfur and / or sulfur allotropes, including orthorhombic, glassy, amorphous and / or polymeric (e.g., β- and / or γ- and / or polymer phase) sulfur, and / or a mixture of two or more sulfur allotropes. Examples of sulfur / sulfur allotropes include cyclic sulfur, amorphous chain sulfur, tad-polephoto sulfur allotropes, copolymerized sulfur doped with other chalcogenides and / or halogen dopants, carbon-sulfur composites including carbon allotropes or defective carbonaceous structures with sulfur and / or other sulfur allotropes, or other sulfide electrode materials. Typically, the electrode is a 3D host including crystalline, amorphous or polymeric (e.g., β- and / or γ- and / or ω-phase) sulfur or a mixture thereof, and such structures are generally known and available to those skilled in the art.
[0185] Figure 5A A flow chart of an example of a method (500A) for producing a coated electrode according to the principles described herein is shown. The method (500A) for producing a coated electrode comprises the following steps: (a) providing a porous sulfur substrate as an electrode material (501); (b) forming a first continuous coating (502) comprising a two-dimensional (2D) material on the sulfur substrate; (c) forming a covalent bond (503) between the 2D material of the first coating and the sulfur substrate; (d) forming a second coating (504) comprising a second 2D material on the first coating.
[0186] Figure 5BA flowchart showing an example of other variations of a method (500B) for producing a coated electrode according to the principles described herein. The method (500B) for producing a coated electrode comprises the following steps: (a) providing a porous sulfur substrate as an electrode material (501); (b) forming (i) a first continuous coating layer comprising a two-dimensional (2D) material on the sulfur substrate; and (ii) a second coating layer comprising a second 2D material on the first coating layer; by using electrostatically driven layer-by-layer assembly (505); (c) forming a covalent bond (503) between the 2D material of the first coating layer and the sulfur substrate. In other words, the step of forming the second coating layer on the first coating layer can be performed before the step of forming the covalent bond (503).
[0187] The method for producing a coated electrode includes a step of forming a first continuous coating layer comprising a two-dimensional (2D) material on a sulfur substrate of an electrode material. The step of forming a first continuous coating layer (502 or 505 (i)) is not particularly limited and includes methods known to those skilled in the art for applying a coating layer on the entire surface of a substrate material, such as dip coating, vacuum filtration, spray coating, spin coating, bar coating, slot coating, roll-to-roll printing, screen printing, flexographic printing, lithography, inkjet printing, or film stretching.
[0188] Figure 6 Schematic diagram (cross section) of an example of a protective layer coating electrode (60) material according to an embodiment of the present disclosure, such as a coated sulfur wafer cathode. The coated electrode includes a porous sulfur substrate (64), a first coating (63) comprising a two-dimensional (2D) material covalently bonded to the sulfur substrate and covering the entire surface of the electrode material, and a second coating (62) comprising a two-dimensional (2D) material on the first coating (63). One surface of the coated electrode faces an electrolyte (61), such as a cathode electrolyte, and one surface of the coated electrode faces a current collector (65).
[0189] Fig. 7A , Figure 7B and Figure 7C An example of an embodiment of a coated battery electrode (70) according to the present disclosure is schematically shown, including a protective layer (72) of a coated electrode material according to an embodiment of the present disclosure and one or more current collector tabs (71) attached thereto. In some embodiments, the protective layer can be used as a current collector. For example, such an electrode can be used as a cathode in an electrochemical cell or battery.
[0190] Figure 8The interaction of lithium ions (81) with an embodiment of a coated electrode (80) according to the present disclosure is schematically shown. The embodiment of the coated electrode includes a porous sulfur substrate (84), a first coating (83) comprising a two-dimensional (2D) material covalently bonded to the sulfur substrate and covering the entire surface of the electrode material, and a second coating (82) comprising a two-dimensional (2D) material on top of the first coating (83).
[0191] Fig. 9 It is a powder X-ray diffraction (p-XRD) pattern of an embodiment of a coated electrode according to the present disclosure. The coated electrode includes a porous sulfur wafer substrate disclosed in WO 2021 / 233965 A1 and a first GO coating formed by dip coating (i.e., immersing an independent porous sulfur wafer in a GO dispersion and then drying) and covalently bonded to the sulfur of the electrode material by irradiation treatment. The coated electrode also includes a second GO coating on top of the first covalently bonded GO / r-GO coating, which is thicker than the first coating and is formed by electrophoretic deposition coating. The diffraction pattern was collected by X-ray powder diffraction measurements on a STOE Stadi MP diffractometer equipped with a Dectris Mythen 1K linear silicon strip detector and a Ge (111) double crystal monochromator (Mo Kα1 radiation) in transmission geometry, confirming the presence of a monoclinic beta (β) phase sulfur allotrope.
[0192] Fig. 10A and 10B The results of a study of the galvanostatic charge / discharge behavior and cycling performance of the pristine sulfur wafer cathode at C / 10 according to WO 2021 / 233965 A1 are shown. Fig. 10C and 10D Results of studies of galvanostatic charge / discharge behavior and cycling performance of embodiments of coated electrodes according to the present disclosure, i.e., GO-coated and irradiated sulfur wafer cathodes, performed at C / 10 are shown. The results indicate that crosslinking between the sulfur electrode material substrate and the graphene oxide coating leads to stable cycling performance and significant improvement in galvanostatic charge / discharge behavior. Cycling measurements were performed on a LAND cycler in galvanostatic mode, using metallic lithium, celgrad 2500 separators, and ether electrolytes, with the provided LAND software (version 7.4).
[0193] Further examples of the present disclosure are summarized in numerical order as follows:
[0194] Example 1. A coated electrode, comprising:
[0195] (a) Sulfur as electrode material;
[0196] (b) a first coating layer comprising a two-dimensional (2D) material and covering the entire surface of the electrode; and
[0197] (c) a second coating layer on top of the first coating layer, the second coating layer comprising a 2D material;
[0198] Characterized in that the first coating is covalently bonded to the sulfur of the electrode material.
[0199] 2. The coated electrode of example 1, wherein the coated electrode comprises at least one substantially flat surface.
[0200] 3. The coated electrode according to example 1 or 2, wherein the electrode is a cathode.
[0201] 4. A coated electrode according to any one of the preceding examples, wherein the electrode material comprises a crystalline sulfur core.
[0202] 5. A coated electrode according to any one of the preceding examples, wherein the electrode material is a porous monolithic sulfur wafer.
[0203] 6. The coated electrode according to any of the preceding examples, wherein the sulfur comprises orthorhombic sulfur, glassy sulfur, amorphous sulfur, polymeric sulfur, a combination of two or more sulfur allotropes, or any combination thereof.
[0204] 7. The coated electrode according to any one of the preceding examples, wherein the sulfur exists in the form of crystals and polymers.
[0205] 8. The coated electrode according to any of the preceding examples, comprising at least one sulfur allotrope doped with a chalcogenide, a halogen or a mixture thereof.
[0206] 9. A coated electrode according to Example 7, wherein the doped sulfur allotrope includes from 0.001 to 10 wt% of chalcogenide, halogen or a mixture thereof, such as 0.01 to 9 wt%, 0.1 to 5 wt%, 0.5 to 4 wt% or 0.75 to 3 wt%, such as 1 wt%, 1.5 wt% or 2 wt% of chalcogenide, halogen or a mixture thereof, based on the total weight of the sulfur allotrope.
[0207] 10. A coated electrode according to any of the preceding examples, comprising 1 to 99 wt % sulfur, such as 20 to 98 wt %, 30 to 97 wt %, 40 to 96 wt %, 50 to 95 wt %, 60 to 94 wt %, 70 to 93 wt % or 80 to 92 wt % sulfur, such as 80, 85, 86, 87, 88, 89 or 90 wt % sulfur, based on the total weight of the coated electrode.
[0208] 11. A coated electrode according to any of the preceding examples, wherein the electrode material comprises an independent monolithic polycrystalline sulfur wafer comprising or consisting of: twinned and / or branched structures of sulfur crystals, such as 1D and / or 2D nanocrystals of monoclinic sulfur.
[0209] 12. A coated electrode according to any one of the preceding examples, wherein the first coating comprises microsheets of 2D material, nanosheets of 2D material or a mixture thereof.
[0210] 13. A coated electrode according to any of the preceding examples, wherein the first coating comprises a charged 2D material.
[0211] 14. A coated electrode according to any one of the preceding examples, wherein the first coating is transparent to ultraviolet light.
[0212] 15. The coated electrode of any preceding example, wherein the first coating is transparent to an electron beam, such as a high energy electron beam.
[0213] 16. A coated electrode according to any of the preceding examples, wherein the first coating is permeable to cations, such as Li+, Na+, Ca2+, Mg2+, Al3+, and is electronically conductive.
[0214] 17. A coated electrode according to any of the preceding examples, wherein the first coating is flexible in volume.
[0215] 18. The coated electrode according to any one of the preceding examples, wherein the first coating layer is a single layer or has a laminated structure.
[0216] 19. A coated electrode according to any of the preceding examples, wherein the first coating is obtainable by electrostatically driven layer-by-layer assembly.
[0217] 20. A coated electrode according to any one of the preceding examples, wherein one or more covalent bonds between the first coating and sulfur of the electrode material are formed by ring-opening polymerization of the sulfur.
[0218] 21. A coated electrode according to any of the preceding examples, wherein the 2D material of the first coating is selected from the group consisting of carbon, graphene, graphene oxide, graphitic carbon nitride, boron nitride, hexagonal boron nitride, aluminum nitride, molybdenum nitride, titanium nitride, silicene, phosphorene, germanene, transition metal dichalcogenides, transition metal oxides, transition metal carbides, transition metal nitrides, or a composite mixture of any two or more of the foregoing.
[0219] 22. A coated electrode according to any one of the preceding examples, wherein the 2D material of the first coating is capable of reacting directly or indirectly with sulfur.
[0220] 23. A coated electrode according to any of the preceding examples, wherein the 2D material of the first coating comprises reduced graphene oxide, such as in situ reduced graphene oxide obtainable by photon-induced ring-opening polymerization of sulfur.
[0221] 24. A coated electrode according to any one of the preceding examples, wherein the 2D material of the first coating comprises a mixture of graphene oxide and reduced graphene oxide.
[0222] 25. A coated electrode according to any of the preceding examples, wherein the 2D material of the first coating is undecorated, functionalized with groups capable of reacting with sulfur, or decorated with metal nanoparticles, metal oxide nanoparticles, metal alloy nanoparticles, non-metal alloy nanoparticles, or a mixture of any of the above.
[0223] 26. A coated electrode according to any one of the preceding examples, wherein the first coating has a thickness of 2 to 45 nm, such as 5 to 35 nm, 8 to 25 nm or 10 to 20 nm, such as 10 nm, 15 nm or 20 nm.
[0224] 27. A coated electrode according to any one of the preceding examples, wherein the first coating has a lower density than the second coating.
[0225] 28. A coated electrode according to any one of the preceding examples, wherein the second coating comprises microsheets of 2D material, nanosheets of 2D material, or a mixture thereof.
[0226] 29. A coated electrode according to any of the preceding examples, wherein the second coating comprises a charged 2D material.
[0227] 30. A coated electrode according to any of the preceding examples, wherein the second coating is permeable to cations, such as Li+, Na+, Ca2+, Mg2+, Al3+, and is electronically conductive.
[0228] 31. A coated electrode according to any of the preceding examples, wherein the second coating is flexible in volume.
[0229] 32. The coated electrode according to any one of the preceding examples, wherein the second coating layer is a single layer or has a laminated structure.
[0230] 33. A coated electrode according to any of the preceding examples, wherein the 2D material of the second coating is selected from the group consisting of carbon, graphene, graphene oxide, graphitic carbon nitride, boron nitride, hexagonal boron nitride, aluminum nitride, molybdenum nitride, titanium nitride, silicene, phosphorene, germanene, transition metal dichalcogenides, transition metal oxides, transition metal carbides, transition metal nitrides, or a composite mixture of any two or more of the foregoing.
[0231] 34. A coated electrode according to any of the preceding examples, wherein the 2D material of the second coating comprises graphene.
[0232] 35. A coated electrode according to any of the preceding examples, wherein the 2D material of the second coating comprises graphene oxide.
[0233] 36. A coated electrode according to any one of the preceding examples, wherein the 2D material of the second coating comprises a mixture of graphene oxide and reduced graphene oxide.
[0234] 37. A coated electrode according to any of the preceding examples, wherein the 2D material of the second coating is undecorated or decorated with metal nanoparticles, metal oxide nanoparticles, metal alloy nanoparticles, non-metal alloy nanoparticles, or any mixture thereof.
[0235] 38. A coated electrode according to any of the preceding examples, wherein the second coating has a thickness of 10 nm to 15 μm, such as 50 nm to 15 μm, 0.5 to 14 μm, 2.5 to 13 μm, 5 to 12 μm or 7.5 to 11 μm, such as 8, 9 or 10 μm.
[0236] 39. A coated electrode according to any of the preceding examples, wherein a portion of the second coating is in direct contact with an electrolyte such as an anode electrolyte or a cathode electrolyte.
[0237] 40. A coated electrode according to any of the preceding examples, wherein a portion of the second coating is in direct contact with the cathode electrolyte.
[0238] 41. A coated electrode according to any of the preceding examples, wherein a portion of the second coating is in direct contact with a current collector.
[0239] 42. A coated electrode according to any of the preceding examples, wherein each of the first and second coatings consists of a single layer.
[0240] 43. The coated electrode according to any one of the preceding examples, wherein the first coating layer consists of a single layer and the second coating layer has a laminated structure.
[0241] 44. The coated electrode according to any one of the preceding examples, wherein the first coating layer has a laminated structure and the second coating layer consists of a single layer.
[0242] 45. A coated electrode according to any one of the preceding examples, wherein each of the first and second coatings has a laminated structure.
[0243] 46. A coated electrode according to any of the preceding examples, wherein the total thickness of the first and second coatings is 12 nm to 15 μm, such as 0.5 μm to 15 μm, such as 2.5 to 14 μm, 5 to 13 μm or 7.5 to 12 μm, such as 8, 9 or 10 μm.
[0244] 47. A coated electrode according to any of the preceding examples, wherein, if present, the first and second coatings comprise 0.1 to 30 wt % of charged 2D material, such as 1 to 25 wt %, 2 to 20 wt %, 3 to 15 wt % or 4 to 12 wt % of charged 2D material, such as 8.5 wt %, 9 wt % or 10 wt % of charged 2D material, based on the total weight of the coated electrode.
[0245] 48. A coated electrode according to any of the preceding examples, wherein the first and second coatings allow photons to penetrate through the thickness of the electrode.
[0246] 49. A primary or secondary energy storage device or electrochemical cell comprising a coated electrode according to any one of Examples 1 to 48.
[0247] 50. The primary or secondary energy storage device or electrochemical cell of Example 49, further comprising at least one electrolyte, such as a liquid electrolyte, a polymer electrolyte, a solid electrolyte, or a mixture thereof.
[0248] 51. The primary or secondary energy storage device or electrochemical cell of Example 49 or 50, further comprising at least one current collector.
[0249] 52. A primary or secondary energy storage device or electrochemical cell according to any one of Examples 49 to 51, wherein the coated electrode is a cathode.
[0250] 53. The primary or secondary energy storage device or electrochemical cell according to any one of Examples 49 to 52, further comprising an alkali metal, an alkaline earth metal, an aluminum metal or a metal alloy as an anode and a porous separator disposed between the cathode and the anode.
[0251] 54. A method for producing a coated electrode, comprising the steps of:
[0252] (a) providing a porous sulfur substrate as an electrode material;
[0253] (b) forming a first continuous coating comprising a two-dimensional (2D) material on the sulfur substrate;
[0254] (c) forming a covalent bond between the 2D material of the first coating and the sulfur substrate;
[0255] (d) forming a second coating layer including a second 2D material on the first coating layer.
[0256] 55. The method of example 54, wherein the first coating of step (b) is formed by dip coating, vacuum filtration, spray coating, spin coating, bar coating, slot coating, roll-to-roll printing, screen printing, flexographic printing, lithographic printing, inkjet printing, or film stretching.
[0257] 56. A method according to any one of Examples 54 or 55, wherein step (c) of forming a covalent bond comprises ring-opening polymerization, such as ring-opening polymerization driven by photons at a certain frequency and / or electrons accelerated to a certain speed.
[0258] 57. A method according to any one of Examples 54 to 56, wherein the second coating of step (d) is formed by electrophoretic deposition of the second 2D material.
[0259] 58. A method for producing a coated electrode, comprising the steps of:
[0260] (a) providing a porous sulfur substrate as an electrode material;
[0261] (b) forming on the sulfur substrate (i) a first continuous coating layer comprising a two-dimensional (2D) material; and (ii) a second coating layer comprising a second 2D material on the first coating layer; by using electrostatically driven layer-by-layer assembly;
[0262] (c) forming a covalent bond between the 2D material of the first coating and the sulfur substrate.
[0263] 59. A method according to any one of Examples 54 to 58, wherein the first coating includes at least graphene oxide as the 2D material.
[0264] 60. The method of any one of examples 54 to 59, wherein the first coating is formed to a thickness of 2 to 45 nm, such as 5 to 35 nm, 8 to 25 nm, or 10 to 20 nm, such as 10 nm, 15 nm, or 20 nm.
[0265] 61. A method according to any one of Examples 54 to 60, wherein the second coating is formed to a thickness of 10 nm to 15 μm, such as 50 nm to 15 μm, 0.5 to 14 μm, 2.5 to 13 μm, 5 to 12 μm or 7.5 to 11 μm, such as 8, 9 or 10 μm.
[0266] 62. A method according to any one of Examples 54 to 61, wherein the second coating comprises at least one charged 2D material.
[0267] 63. The method of any one of examples 54 to 62, further comprising the steps of:
[0268] (e) connecting a current collector to the coated electrode obtained through steps (a) to (d).
[0269] 64. An electrode and / or cathode stabilized by a transition layer, comprising:
[0270] (a) A porous chalcogenide-based electrode, more preferably sulfur, comprising primarily a crystalline allotrope within the core;
[0271] (b) at least one of a glass, a polymer and an amorphous chalcogenide, more desirably a sulfur allotrope, present in a transition layer and / or a shell covering the surface of an active electrode material, the transition layer comprising a two-dimensional (2D) material, covalently bonded between the chalcogenide, more desirably sulfur, of the electrode material, and 12 wt % or less of polymeric sulfur based on the total weight of the coated electrode; and
[0272] (c) a coating layer on top of the transition layer, the coating layer comprising a 2D material,
[0273] (d) There is a density gradient between the crystalline core and the glass / polymer / amorphous shell,
[0274] (e) an electrode, wherein the volume of the crystalline allotrope present in the internal voids represents a buffer volume for compensating for volume fluctuations during battery cycling,
[0275] (f) Chalcogenide electrodes, more preferably sulfur-rich electrodes, wherein the electrode active material is composed of binary and / or ternary dopants such as selenium and tellurium, having a composition (Se x S y )、(Te x S y )、(Te x S y Se z ), wherein the mass content of sulfur in the cathode is higher than 50% per weight of the total chalcogenide content, wherein
[0276] (g) A coated electrode and / or cathode comprising at least one sulfur allotrope doped with a chalcogenide, a halogen, or a mixture thereof, more desirably comprising from 0.001 to 50 wt % of the chalcogenide, the halogen, or a mixture thereof, such as 0.01 to 49 wt %, 0.1 to 45 wt %, 0.5 to 44 wt %, or 0.75 to 43 wt %, such as 1 wt %, 1.5 wt %, or 2 wt % of the chalcogenide, the halogen, or a mixture thereof, based on the total weight of the sulfur allotrope.
[0277] 65. A method for producing an electrode and / or a cathode, comprising the steps of:
[0278] a. providing a crystalline chalcogenide allotrope nucleus, more preferably a sulfur nucleus,
[0279] b. forming a first photon / electron irradiation transparent material coating comprising graphene oxide on the surface of the electrode and / or cathode,
[0280] c. exposing the electrode to photon and / or electron irradiation to induce ring-opening polymerization of crystalline sulfur to form an amorphous sulfur shell on the crystalline sulfur core, wherein graphene oxide reacts by ring-opening polymerization of crystalline sulfur induced by photon and / or electron irradiation and is deoxidized by in-situ reduction to form reduced graphene oxide, and
[0281] d. covalently bonding the layer comprising reduced graphene oxide to the amorphous sulfur shell.
[0282] It should be noted that the description and drawings are merely illustrative in nature and are not intended to limit the scope of the present disclosure, which is defined by the appended claims.
Claims
1. An electrode, optionally a cathode, stabilized by a transition layer as a first coating, the electrode comprising: (a) a porous chalcogenide-based electrode material, more desirably sulfur, comprising primarily a crystalline allotrope within the core of the electrode, with a shell covering the surface of the electrode material; (b) at least one of a glass, a polymer and an amorphous chalcogenide, more preferably a sulfur allotrope, present in the transition layer and / or the shell covering the surface of the active electrode material, the transition layer comprising a two-dimensional (2D) material, covalently bonded between the chalcogenide, more preferably sulfur, of the electrode material, and 12 wt% or less of polymeric sulfur based on the total weight of the coated electrode; and (c) a second coating layer on top of the transition layer, the coating layer comprising a 2D material, (d) there is a density gradient between the crystalline core and the glass / polymer / amorphous shell, (e) wherein the volume of the crystalline allotrope present in the internal voids of the core represents a buffer volume for compensating for volume fluctuations during battery cycling, (f) wherein the electrode active material is composed of binary and / or ternary dopants such as selenium and tellurium, and has a composition (Se x S y )、(Te x S y )、(Te x S y Se z ), wherein the mass content of sulfur in the electrode is higher than 50% of the total chalcogenide content per weight, wherein (g) the coated electrode comprises at least one sulfur allotrope doped with a chalcogenide, a halogen or a mixture thereof, more desirably comprising from 0.001 to 50 wt % of the chalcogenide, the halogen or a mixture thereof, such as 0.01 to 49 wt %, 0.1 to 45 wt %, 0.5 to 44 wt % or 0.75 to 43 wt %, based on the total weight of the sulfur allotrope, Such as 1 wt%, 1.5 wt% or 2 wt% of chalcogenide, halogen or mixtures thereof.
2. The electrode according to claim 1, wherein a. the glassy / amorphous chalcogenide, more preferably the sulfur shell, is the product of photon and / or electron irradiation induced ring-opening polymerization of crystalline chalcogenide allotropes, and b. the transition layer is the product of photon and / or electron irradiation through a transparent graphene oxide layer coated on a crystalline allotrope of a chalcogenide, preferably sulfur core, wherein the photon and / or electron irradiation induces a ring-opening polymerization ROP of the chalcogenide, preferably sulfur, and an in-situ reduction of the graphene oxide to reduced graphene oxide, c. the in situ formed transition layer is covalently bonded to the surface of the chalcogenide active material, preferably sulfur, d. The transition layer is rich in negatively charged surface functional groups, optionally thiols, thioethers, sulfoxides, sulfones and sulfonic acids), resulting from photon and / or electron induced ROP of chalcogenides, more ideally sulfur, and deoxidation of graphene oxide to reduced graphene oxide, where the negatively charged surface acts as a polysulfide blocking intermediate layer.
3. The electrode according to claim 1 or 2, wherein The photon / electron irradiation has at least one of the following characteristics: the wavelength of the photon irradiation is between 450nm and 120nm in terms of light / UV, and is 10 -12 m to 10 -16 m, and the electron irradiation energy is at least 5 MeV.
4. An electrode according to any one of the preceding claims, wherein The covalent bonds between the transition layer comprising reduced graphene oxide and the amorphous chalcogenide, more desirably the sulfur shell, are the product of providing gaseous and / or vaporous and / or liquid comonomers penetrating the inner cavity of the chalcogenide electrode, wherein under the influence of irradiation, a chalcogenide-rich copolymer is formed together with the transition layer comprising reduced graphene oxide.
5. An electrode according to any one of the preceding claims, wherein The first coating and / or the first and second coatings are permeable to cations such as Li + 、Na + , K + , Ca 2+ 、Zn 2+ Mg 2+ 、Al 3+ , but not limited thereto, and is electronically conductive, wherein optionally, The electrode is a glass and / or crystalline chalcogenide cathode composed of a metastable crystalline, optionally monoclinic gamma-γ-sulfur core stabilized by a glass / polymer / amorphous chalcogenide shell supported by the transition layer, wherein optionally the transition layer is the transition layer comprising reduced graphene oxide, wherein optionally the shell is an in situ formed glass / polymer / amorphous shell.
6. An electrode according to any one of the preceding claims, wherein The 2D material of the first coating is functionalized with groups capable of reacting with the chalcogenide, preferably sulfur, and / or decorated with metal nanoparticles, metal oxide nanoparticles, metal alloy nanoparticles, non-metal alloy nanoparticles or mixtures of any of the above, and / or Wherein, the first coating has a thickness of 0.3 to 500 nm, such as 5 to 500 nm, 8 to 250 nm or 10 to 200 nm, such as 1 nm, 10 nm, 100 nm, 150 nm or 200 nm, wherein the second coating comprises microsheets of 2D material, nanosheets of 2D material and / or charged 2D material and / or a mixture thereof.
7. An electrode according to any one of the preceding claims, wherein A second 2D material layer is provided, coating the electrode over the transition layer comprising reduced graphene oxide.
8. An electrode according to any one of the preceding claims, wherein The layers are obtained by layer-by-layer assembly, optionally electrostatically driven layer-by-layer assembly, spin coating, bar coating, slot coating, roll-to-roll printing, screen printing, flexographic printing, lithographic printing, inkjet printing or film stretching.
9. An electrode according to any one of the preceding claims, wherein The 2D material of the second coating is selected from the group consisting of carbon, graphene, graphene oxide, graphitic carbon nitride, hexagonal boron nitride, aluminum nitride, molybdenum nitride, titanium nitride, silicene, phosphorene, germanene, transition metal dichalcogenides, transition metal oxides, transition metal carbides, transition metal nitrides or a composite mixture of any two or more of the foregoing, wherein, more ideally, the second layer comprises graphene and / or graphene oxide and / or a mixture of graphene oxide and reduced graphene oxide.
10. An electrode according to any one of the preceding claims, wherein The second coating and / or the first and second layers are permeable to cations such as Li + 、Na + , K + , Ca 2+ 、Zn 2+ Mg 2+ 、Al 3+ , but not limited to, and / or are electronically conductive.
11. An electrode according to any one of the preceding claims, wherein The second coating has a thickness in the range of 0.3 nm to 15 μm, such as 50 nm to 15 μm, 0.5 to 14 μm, 2.5 to 13 μm, 5 to 12 μm or 7.5 to 11 μm, such as 8, 9 or 10 μm.
12. An electrode according to any one of the preceding claims, wherein A portion of the second coating transition layer is in direct contact with the electrolyte between the electrodes and / or is in indirect mediated contact with a cathode electrolyte present within the electrodes and / or wherein a portion of the second coating is in direct contact with the current collector.
13. An electrode according to any one of the preceding claims, wherein The total thickness of the first and second coatings ranges from 0.3 nm to 15 μm, such as 0.5 μm to 15 μm, such as 2.5 to 14 μm, 5 to 13 μm or 7.5 to 12 μm, such as 8, 9 or 10 μm, more ideally 10 to 200 nm.
14. A method for producing an electrode, optionally a cathode, comprising the steps of: a. providing a crystalline chalcogenide allotrope nucleus, more preferably a sulfur nucleus, b. forming a first photon / electron irradiation transparent coating of a material including graphene oxide as a transition layer on the surface of the electrode, c. exposing the electrode to photon and / or electron irradiation to induce ring-opening polymerization of crystalline sulfur to form a glass / polymer / amorphous sulfur shell on the crystalline sulfur core, wherein graphene oxide reacts by ring-opening polymerization of crystalline sulfur induced by photon and / or electron irradiation and is deoxidized by in-situ reduction to form reduced graphene oxide, and d. covalently bonding the transition layer comprising reduced graphene oxide to the amorphous sulfur shell.
15. The method according to claim 14, wherein: The step of forming covalent bonds between the transition layer comprising reduced graphene oxide and the amorphous chalcogenide shell, more preferably the sulfur shell, is performed by providing a gaseous and / or vaporous and / or liquid comonomer and converting the crystalline sulfur at the GO and / or sulfur interface into a sulfur-rich copolymer using photon and / or electron irradiation and crosslinking the sulfur and / or sulfur allotrope of the electrode material with the transition layer comprising reduced graphene oxide.
16. The method according to claim 14 or 15, further comprising the step of coating the electrode with a second 2D material layer over the transition layer comprising reduced graphene oxide.
17. The method according to claim 14, wherein: The first coating layer of step b is formed by dip coating, vacuum filtration, spray coating, layer by layer, spin coating, bar coating, slot coating, roll-to-roll printing, screen printing, flexographic printing, lithography, inkjet printing or film stretching.
18. The method according to any one of claims 14 to 17, wherein: The second coating is formed by electrophoretic deposition and / or reduction of the second 2D material.
19. A primary or secondary energy storage device, or electrochemical cell, comprising an electrode according to any one of claims 1 to 13, and produced according to the method of any one of claims 14 to 18.
20. The primary or secondary energy storage device, or electrochemical cell, of claim 19, further comprising at least one electrolyte, such as a liquid electrolyte, a polymer electrolyte, a gel electrolyte, a solid electrolyte, a cathode electrolyte, a composite electrolyte and / or a mixture thereof.
Citation Information
Patent Citations
Advanced monolithic sulphur wafer-like cathode based on hyper-branched super-structures and method of manufacture thereof
WO2021233965A1